2022
DOI: 10.1111/josi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Who supports #MeToo and the Kavanaugh confirmation? Exploring tolerance for sexual harassment among young adults

Abstract: Young adults have become increasingly involved in political and social movements around sexual harassment. This involvement likely reflects political identity as well ideological beliefs about sexual harassment. We examined how young adults’ ideological beliefs and political party identity are associated with their tolerance of sexual harassment, support for the #MeToo movement and the confirmation of Justice Kavanaugh. Tolerance for sexual harassment was positively associated with endorsement of rape myth acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Sexual harassment (SH) is and has been a pervasive social issue in the United States. While not a new issue, recent events such as the broader recognition and social media spread of the #MeToo movement, the Brett Cavanaugh confirmation hearings, and the resignation of Anthony Cuomo have catapulted SH into public discourse in ways we have not seen before (Crowley et al., 2018; Oswald & Herrera Hernandez, 2023). The increased attention to SH in public discourse has also made more evident the range of attitudes and beliefs about this type of harassment within society (e.g., when these behaviors are wrong or harmful; if and how to hold people accountable for their actions).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual harassment (SH) is and has been a pervasive social issue in the United States. While not a new issue, recent events such as the broader recognition and social media spread of the #MeToo movement, the Brett Cavanaugh confirmation hearings, and the resignation of Anthony Cuomo have catapulted SH into public discourse in ways we have not seen before (Crowley et al., 2018; Oswald & Herrera Hernandez, 2023). The increased attention to SH in public discourse has also made more evident the range of attitudes and beliefs about this type of harassment within society (e.g., when these behaviors are wrong or harmful; if and how to hold people accountable for their actions).…”
Section: Introductionmentioning
confidence: 99%
“…In their scoping review, Bolduc et al (2022) put the spotlight on how the sexual harassment research field is marked by heterogeneity in terms of theoretical perspectives, and how this heterogeneity in turn influences what types of correlates empirical studies focus on. Several of the correlates proposed within different theoretical frameworks are also reflected by the papers published in this special issue, for example, minority status, pubertal development, and norms and attitudes (Erentzen et al, 2022;Herrera Hernandez & Oswald, 2022;Honkatukia et al, 2022;Horn & Poteat, 2022;Li et al, 2022;Ormerod et al, 2022;Ringrose & Regehr, 2023;Skoog & Kapetanovic, 2022). As noted by Bolduc and colleagues, more seldomly have research studies integrated the established correlates of sexual harassment within the same study.…”
Section: Innovative Approaches and Methods Advance The Current Knowle...mentioning
confidence: 94%
“…More tolerant attitudes were also held during times when sexual harassment was more frequent, indicating that these actions were then more justified in young people's attitudes. Further, Herrera Hernandez and Oswald (2022) found that young people's tolerance of sexual harassment was associated with more endorsement of rape myth acceptance and sexism, indicating that tolerance of sexual harassment is tied to tolerance of gender inequality and sexual violence more generally. Targeting young people's attitudes toward sexual harassment, or their attitudes toward sexual aggression more broadly, could be one way to address the problem of sexual harassment among young people.…”
Section: Cross‐cutting Themesmentioning
confidence: 99%
See 2 more Smart Citations